Literature review using the concept of Value Stream Mapping in the manufacturing industry - Antonio, Tito; Anggara, Sunu Surya; Sedubun, Elkiopas; Nurhaliza, Siti Farah; Setiawan, Rohmat; Setiawan, Indra; Azzahra, Shafa (Universitas Sultan Ageng Tirtayasa, 2023)
Value Stream Mapping (VSM) has become a valuable tool for decision-making and identifying opportunities for lean manufacturing practices. This study reviewed literature from various sources, including Google Scholar and Science Direct, to explore the application of VSM in different sectors of the manufacturing industry. The study used specific keywords, such as